A new species of Rhagovelia Mayr, 1865 (Hemiptera: Heteroptera: Veliidae) from French Guiana, with new records of Gerromorpha from the country - Da Motta, Flávia Souza; Moreira, Felipe Ferraz Figueiredo; Crumière, Antonin Jean Johan; Santos, Maria Emília; Khila, Abderrahman (Zootaxa, 2018)
Rhagovelia apuruaque sp. nov. (Hemiptera: Heteroptera: Veliidae), from the commune of Régina, French Guiana, is described, illustrated, and compared with species of the salina group. Brachymetra albinervus (Amyot & Serville, 1843), B. lata Shaw, 1933, Limnogonus ignotus Drake & Harris, 1934, Neogerris lubricus (White, 1879), Rheumatobates crassifemur esakii Schroeder, 1931 (Gerridae), Mesovelia mulsanti White, 1879 (Mesoveliidae), Microvelia longipes Uhler, 1894, M. mimula White, 1879, M. pulchella Westwood, 1834, R. humboldti Polhemus, 1997, and S. transversa (Hungerford, 1929) (Veliidae) are recorded for the first time from French Guiana. The presence of Tachygerris adamsoni (Drake, 1942) (Gerridae) in the country is confirmed. New records are presented for the following species previously reported from the study area: B. shawi Hungerford & Matsuda, 1957, Cylindrostethus palmaris Drake & Harris, 1934, L. hyalinus (Fabricius, 1803) (Gerridae), Husseyella turmalis (Drake & Harris, 1933), Paravelia bullialata Polhemus & Polhemus, 1984, and Stridulivelia strigosa (Hungerford, 1929) (Veliidae).